The Philosophy of Geography
VIII, 244 p. 15 illus., 10 illus. in color.
Keywords: The relationship between geography and philosophy is still largely in need of being explored. Geographers and philosophers share the responsibility for that. On the one hand, geographers have considered as a dangerous deviation any attempt to elaborate an image of the Earth which was not a mere replica of a cartographic representation. On the other hand, philosophers have generally been uninterested in a discipline offering little chance for critical reflection. In light of these considerations, the purpose of this book is to identify some fundamental philosophical issues involved in the reflection of geography by adopting a perspective which looks at the discipline with a specific focus on its fundamental concepts and distinctions.